ANALISIS DISIPLIN KERJA SUMBER DAYA MANUSIA PADA KARYAWAN CV. ASAKOTA KOTA BIMA - Purnawati Purnawati; Firmansyah Kusumayadi (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine how the level of work discipline of human resources in employees of CV. Asakota Bima City. The instrument in this study used a questionnaire with a Likert scale. The population in this study amounted to 50 employees at CV. Asakota Bima City with saturated sampling technique. Data collection techniques using observation, interviews, questionnaires and documentation. The data analysis technique used validity test, reliability test, and one sample t-test test using SPSS version 22 for windows. Based on the results of the one sample t-test on the discipline of human resources work on employees of CV. Asakota Kota Bima is said to meet the criteria or is good because it is more than 75%, where the work discipline of employees is CV. Asakota Kota Bima is in accordance with the wishes expected by the company with a value level of t-count t-table (56.357 2.010), stating that Ho is rejected and Ha is accepted with a significant value of 0.000 0.05, which means significant.